Effect of Heat Treatment and 1,5% Magnesium Addition on Density, Hardness, and Tensile Strength of Al-Cu-Mg Alloys - Junipitoyo, Bambang; Said, Djamaaludin; Dwiyanto, Dwiyanto (Nusantara Publisher, 2024)
This research focuses on adding aluminum 1100 combinations by adding magnesium (Mg) as much as 1.5% and varying the percentage of copper (Cu). 3.9%, 4.1%, 4.3%/ with heat treatment at temperatures of 1000C, 2000C, 3000C, and 4000C with a holding time at each temperature of 120 minutes, then tested the aluminum combination's density, Vickers hardness, and tensile strength. The final results of this study showed that in the density test, the highest density value obtained was 4.24 gr/cm3 in a mixture of 1.5% magnesium and 4.3% copper (Cu) with a temperature of 2000C. In the Vickers hardness test, the highest hardness value was 83.9 HVN in a mixture of 1.5% magnesium and 4.3% copper with a temperature of 4000C. The final result of the research conducted was to obtain the tensile strength results of each specimen by obtaining the maximum tensile strength of the 4.1% Cu mixture specimen with a temperature of 4000C of 163.2698 Mpa and the highest strain value in the 4.3% Cu mixture specimen with a temperature of 4000C of 0.0472 %, for the results of the lowest elastic modulus value in the 4.3% Cu mixture specimen with a temperature of 2000C of 3147.319 Mpa and the highest value of the 4.1 % Cu mixture specimen with a temperature of 4000C of 5947.898 Mpa.